2002
DOI: 10.1074/jbc.m105432200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functionally Important Residues of the Epidermal Growth Factor-2 Domain of Factor IX by Alanine-scanning Mutagenesis

Abstract: This paper describes the consequences of alaninescanning mutagenesis on 28 positions of the second epidermal growth factor (EGF-2) domain of factor IX. We identified four positions of Gln 97 , Phe 98 , Tyr 115 , and Leu 117 that are critical for secretion of factor IX. Of the remaining mutations, 4 mutants (V86A, E113A, K122A, and S123A) are as active as wild-type factor IX (IXwt); 16 (D85A, K100A, N101A, D104A, N105A, R116A, E119A, T87A, I90A, K91A, R94A, E96A, S102A, K106A, T112A, and N120A) retain reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 41 publications
(55 reference statements)
2
45
1
Order By: Relevance
“…However, all of these mutations interfere with other activities of FIX in addition to activation by factor XIa. A rFIX protein containing the factor VII EGF1 domain is activated normally by factor XIa (53,54), whereas a study employing alanine scanning mutagenesis on portions of the EGF2 domain identified only a single amino acid (position 89) that appeared to be necessary for normal activation by factor XIa (55).…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these mutations interfere with other activities of FIX in addition to activation by factor XIa. A rFIX protein containing the factor VII EGF1 domain is activated normally by factor XIa (53,54), whereas a study employing alanine scanning mutagenesis on portions of the EGF2 domain identified only a single amino acid (position 89) that appeared to be necessary for normal activation by factor XIa (55).…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation Assays-Activated partial thromboplastin time assays for the seven "candidate" alanine mutants were previously reported (8) and are listed in Table IV, which confirms the physiological function of the interrupted surface binding property of the FIX mutants in mediating clotting. The three mutants N89A (0.5%), I90A (7%), and V107A (0.5%) exhibited the lowest clotting activities.…”
Section: Egf2 Domain Of Fixa In Fx Activation On Plateletsmentioning
confidence: 76%
“…Earlier time-course solution-phase FIX activation results have shown that FXIa activates all the seven FIX alanine mutants at normal rates compared with native FIX (8), and each of the FIX proteins was fully activated by FXIa in solution. Gelcode Blue-stained gels of SDS-PAGE displayed complete disappearance of the zymogen band (ϳ70 kDa) and appearance of heavy (ϳ28 kDa) and light chains (ϳ18 kDa) of FIXa for all the recombinant FIXa proteins (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations